2022
DOI: 10.3390/w14213529
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of an Urban Stormwater Infiltration Trench in South Korea with Assessment Using the Analytic Hierarchy Process

Abstract: Evaluating the functionality of small and decentralized low-impact development (LID) technologies often requires extensive labor, time, and costs for water quality analysis. In order to reduce these in an infiltration trench in South Korea, monitoring data gathered over a period of 8 years were used to determine its long-term performance, establish a stormwater quality estimation model, and develop a comprehensive evaluation tool. Our findings show that the infiltration trench can treat up to 90% of the stormw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Stormwater filters have been widely reported to achieve the effective net removal of total P when phosphorous is primarily bound to particles [14,24,46]. Reactive filter materials reach moderate levels of dissolved PO 4 removal [14], but the leaching of PO 4 from the filters has been reported to be an issue in some cases [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stormwater filters have been widely reported to achieve the effective net removal of total P when phosphorous is primarily bound to particles [14,24,46]. Reactive filter materials reach moderate levels of dissolved PO 4 removal [14], but the leaching of PO 4 from the filters has been reported to be an issue in some cases [24].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of these changes are not entirely known or well documented; therefore, repeated surveys are necessary to provide information regarding the life cycle and maintenance needs of the filters. Jeon et al [46] gathered monitoring data from a roadside infiltration trench over a period of 8 years and they found that annual maintenance was needed in order to avoid a reduction in the infiltration capacity and treatment performance. It is evident that the filtration of stormwater at times of sustained runoff generation and limited source area concentration leads to the filters being rather a source than a sink for common water quality constituents.…”
Section: Discussionmentioning
confidence: 99%